Counteracting cocaine production. An analysis based on a novel dataset - Riccardo Leoncini; Francesco Rentocchini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2010)
he debate about the effectiveness of the counteracting policies against the supply of drugs, in particular of cocaine, is very lively and intense. Indeed, since many opinions are based on certain measures rather than others, the construction of reliable indicators is one of the preconditions for a correct and concerted assessment of drug supply. The lack of reliable data on drug provision derives, on the one side, from the objective difficulties encountered in assessing the quantitative elements of drug production and drug trafficking due to its illegal nature, and, on the other side, from the lack of a standard methodological approach to the issue. This paper tries to contribute to the topic by proposing a new dataset, based on a completely new approach to the problem of measuring drug supply. We put forward a unique dataset covering cocaine related seizures in Colombia for the whole of year 2008. Data have been collected on a daily basis from the websites of the main organizations fighting against drug traffickers (Army, Air Force, National Police, Departamento Administrativo de Seguridad, Armada Nacional, Fiscalia), detailing each single seizure of laboratories for the production of both basic paste and cocaine hydrochloride. By means of this dataset, we offer some accounts of the main numbers on drug supply and on drug seizures, suggesting some policy options, and arriving to an estimate of cocaine production.
Keywords: K42; C81; D78; 330